2002
DOI: 10.1007/s005350200078
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxy-3-methylglutaryl coenzyme A reductase activity and low-density lipoprotein receptor expression in diffuse-type and intestinal-type human gastric cancer

Abstract: These findings show different behavior of cholesterol metabolism in the two types of gastric carcinoma and, therefore, suggest that different therapeutic strategies should be adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…High levels of 3-hydroxy-3-methylglutaryl coenzyme A reductase [21], farnesyl pyrophosphate synthase [22] and farnesyltransferase [23] have been found in human colon cancers; therefore, we suggested a key role of these enzymes in the process of colon malignant transformation. In addition, we have demonstrated that overexpression of these enzymes is associated with some genetic alterations commonly involved (such as K-ras and p53 gene mutations) in colon cancer development [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of 3-hydroxy-3-methylglutaryl coenzyme A reductase [21], farnesyl pyrophosphate synthase [22] and farnesyltransferase [23] have been found in human colon cancers; therefore, we suggested a key role of these enzymes in the process of colon malignant transformation. In addition, we have demonstrated that overexpression of these enzymes is associated with some genetic alterations commonly involved (such as K-ras and p53 gene mutations) in colon cancer development [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies have shown an association between obesity and functional bowel disorders [17, 18], pointing to obesity as a risk factor for colorectal cancer due to chronic inflammation of colon tissue [19]. All this evidence led us to study the activity and gene expression of FAS, a critical enzyme involved in human colorectal cancer, in which other enzymes of the lipid pathway have already been studied [20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…In a randomized prospective controlled trial, RYR, in comparison to a placebo, decreased total cholesterol, triglycerides, and apolipoprotein B in hypercholesterolemic individuals (Lin et al 2005). Cholesterogenesis is a key factor for tumor growth and HMG-CoA reductase activities are up-regulated in colon tumors (Buchwald 1992;Hentosh et al 2001;Notarnicola et al 2004;Caruso et al 2002). The pharmacological evidences showed that statins may inhibit colon cancer cell growth and thereby reduces incidence of colon cancer (Agarwal et al 2002;Ukomadu and Dutta 2003;Lin et al 2006).…”
Section: Effect Of Ryr In the Treatment Of Cancermentioning
confidence: 94%
“…In particular, low serum HDL-cholesterol was reported to be a negative prognostic factor for gastric adenocarcinoma patients (26). Low-density lipoprotein receptor (LDLR) levels in diffuse type gastric adenocarcinoma were significantly lower than those in normal mucosa, but there was no significant difference between intestinal-type gastric adenocarcinoma and normal mucosa (27). Caveolin-1 is a scaffolding protein that binds to cholesterol and is involved in intracellular cholesterol trafficking.…”
Section: Sr-bi Expression % (N) -----------------------------------mentioning
confidence: 99%